VALUASI EKONOMI DAN DAMPAK WISATA PANTAI TANJUNG PASIR TERHADAP SOSIAL EKONOMI MASYARAKAT SEKITAR DI KABUPATEN TANGERANG - Futakhah, Siti; Prasmatiwi, Fembriarti Erry; Marlina, Lina (Lampung University, 2024)
This study aims to examine the factors that influence the number of tourists who visit Tanjung Pasir Beach, the economic value of tourism, and the impact of tourism on Tangerang Regency's economy. A survey was used in this study, with 77 visitors, 15 businessmen, and a tourism manager responding to the survey. The Tanjung Pasir Beach was selected intentionally as the location for the research. The collection of data was conducted in January - February 2023. This study employed the travel cost, multiple linear regression, and Keynesian multiplier effect as data analysis techniques. The findings revealed that visitors spent IDR102,493.51 per individual per visit on transportation. Distance, age, income, travel costs, facilities, and infrastructure are all factors that influence the number of tourist visits. The result of the calculation of travel cost using TCM on Tanjung Pasir Beach has a yearly economic value of IDR 44,801,325,052. The multiplier effect is used to estimate the economic impact of Tanjung Pasir Beach tourism, which has a direct impact of IDR 193,031,663.83 per month, an indirect impact of IDR 116,505,417.50 per month, and a secondary impact of IDR 80,166,666.67 per month. Tanjung Pasir Beach tourism still has a low impact on the economy because the Keynesian income multiplier value is 0.04. Key words: economic impact, economic value, tourism, travel cost